2007
DOI: 10.1016/j.neulet.2007.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-striatal connections in the human brain: A probabilistic diffusion tractography study

Abstract: Anatomical studies in animals have described multiple striatal circuits and suggested that subcomponents of the striatum, although functionally related, project to distinct cortical areas. To date, anatomical investigations in humans have been limited by methodological constraints such that most of our knowledge of fronto-striatal networks relies on nonhuman primate studies. To better identify the fronto-striatal pathways in the human brain, we used Diffusion Tensor Imaging (DTI) tractography to reconstruct ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
264
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(306 citation statements)
references
References 50 publications
(55 reference statements)
38
264
1
3
Order By: Relevance
“…This connection is supported by the evidence that the basal ganglia-thalamus is anatomically connected with the temporal cortex (e.g., Behrens et al, 2003;Leh et al, 2007;Middleton and Strick, 1996). Moreover, functional connections also exist because the posterior temporal cortex as well as the SMA and basal ganglia have been found to be involved in auditory-motor representations and temporal sequence control of movement regardless of the modality (Karabanov et al, 2009;Kimura et al, 2008;Remy et al, 2008).…”
Section: Connectivity Between the Basal Ganglia-thalamus And The Tempmentioning
confidence: 82%
“…This connection is supported by the evidence that the basal ganglia-thalamus is anatomically connected with the temporal cortex (e.g., Behrens et al, 2003;Leh et al, 2007;Middleton and Strick, 1996). Moreover, functional connections also exist because the posterior temporal cortex as well as the SMA and basal ganglia have been found to be involved in auditory-motor representations and temporal sequence control of movement regardless of the modality (Karabanov et al, 2009;Kimura et al, 2008;Remy et al, 2008).…”
Section: Connectivity Between the Basal Ganglia-thalamus And The Tempmentioning
confidence: 82%
“…Striato-cortico-striatal loops predominantly involving prefrontal cortex (PFC) projections have been delineated in nonhuman primates (Alexander et al, 1986), and confirmed in humans with diffusion tensor imaging (Leh et al, 2007;Lehericy et al, 2004) and resting-state functional magnetic resonance imaging (rs-fMRI) (Di Martino et al, 2008). These loops include: a ventral circuit anchored in the inferior limbic subdivision of the striatum and comprising connections with orbitofrontal cortex (OFC), ventromedial PFC, medial thalamus, and limbic regions that is fundamental to associative learning and reward-mediated decision making (Knutson and Cooper, 2005); and a dorsal circuit, including the associative subdivision of the striatum, dorsolateral PFC and mediodorsal and ventroanterior thalamus that maintains information relating to reward outcomes (O' Doherty et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…The prefrontal cortex (PFC), which includes the dorsolateral prefrontal cortex (DLPFC), orbital frontal cortex (OFC) and the inferior frontal cortex (IFC), plays a central role in executive functioning through its influence on subcortical and posterior cortical regions via extensive anatomical connections to these areas (Croxson et al, 2005;Leh et al, 2007). Recent evidence suggests that successful response inhibition is mediated through striatal dopamine receptors in this frontal-striatal circuit (Ghahremani et al, 2012), and that increased activation of this network is associated with improvement in response-inhibition performance (Congdon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%